Perancangan Aplikasi Quiz Interaktif Berbasis Multimedia Menggunakan UML dan MDLC - Much Nur Syams Simaja; Ali Ikhwan; Fakhri Alauddin Tarihoran; Dzakwan Abbas (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
This study aims to design a multimedia-based interactive quiz application prototype as a digital learning evaluation medium. The main problem addressed is that conventional assessment media do not always provide an integrated timer, automatic scoring, answer discussion, leaderboard, and question management. The research applies a Research and Development approach using the Multimedia Development Life Cycle (MDLC), consisting of concept, design, material collecting, assembly, testing, and distribution stages. System modeling is performed using Unified Modeling Language (UML), including a use case diagram, student activity diagram, admin activity diagram, and class diagram. The result is a system design and interface prototype that includes login, quiz selection, timer-based question answering, score calculation, answer discussion, leaderboard, and question management by the admin. Evaluation is conducted using black-box testing at the prototype level to verify feature conformity with requirement scenarios. The evaluation results indicate that all main scenarios have been represented in the prototype design. This study provides a foundation for further development into a fully functional application and user usability testing.